Integrating Waqf in Shariah-Compliant Asset and Wealth Management - Ghazy Triyatno; Yuniarti Hidayah Suyoso Putra (Talaa : Journal of Islamic Finance, 2025)
The research is motivated by the growing importance of Islamic wealth instruments, particularly waqf, in promoting inclusive and sustainable economic development. The central problem addressed is the underutilization of waqf assets, which is attributed to limited public awareness, fragmented regulations, and a lack of integration with modern financial systems. Therefore, the study aims to investigate the models, instruments, regulatory frameworks, and technological innovations that facilitate the effective integration of waqf into Islamic financial planning. Employing a Systematic Literature Review (SLR) approach, the study identifies 70 relevant articles published between 2015 and 2025 using Scopus and snowball sampling techniques. The analysis involves bibliometric tools (VOSviewer and Publish or Perish) and thematic content analysis to map trends, collaboration networks, and knowledge gaps. The findings reveal four dominant themes: (1) direct and indirect waqf integration models, (2) innovations in waqf-based financial instruments (e.g., CWLS, unit trust waqf, waqf-based insurance), (3) the importance of national and global regulatory alignment, and (4) the transformative role of technology, such as e-waqf and blockchain. These insights affirm that waqf has evolved into a key pillar of Islamic wealth management, offering strategic solutions for economic empowerment and social justice.